Caroline takes a chance, 1812 - Ernst, Kathleen, 1959- (American girls collection., 2012)
"While Caroline is out fishing one spring day, she sees a British warship about to capture an American boat. With only an instant to decide what to do, Caroline takes a daring risk to try to save the day. She's been trying to be brave, like she promised Papa, but would he be proud of her now? Missing him terribly, Caroline visits their special fishing spot on the shore of Lake Ontario. She hopes to find comfort there-- but instead she makes a startling discovery! The illustrated "Looking Back" section discusses transportation and medicine in the early 1800s" -- from publisher's web site.